Analisis Kebijakan Program Pengentasan Kemiskinan di Kota Palangkaraya dalam Mendukung Pencapaian SDGs 1 dan SDGs 8 - Acep Kurniawan; Daniel Daniel; Renno Sambawe; Andika Sanjaya (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
Poverty remains one of the major social issues that continues to receive attention from both central and regional governments. This study aims to analyze poverty alleviation policies implemented in Palangka Raya in supporting the achievement of the Sustainable Development Goals (SDGs), particularly SDGs 1 (No Poverty) and SDGs 8 (Decent Work and Economic Growth). This study employed a qualitative method with a descriptive and library research approach. Data were collected through documentation studies from the Central Statistics Agency (BPS), local government documents, scientific journals, and other relevant literature. The findings show that the poverty rate in Palangka Raya decreased from 3.70% in 2020 to 3.52% in 2024. The Urban Poverty Alleviation Program (P2KP) contributed to improving community welfare through business capital assistance, skills training, and community economic empowerment. However, the implementation of the program still faces several challenges, including limited resources, unequal economic access, and weak program monitoring systems. Therefore, stronger coordination among institutions and improvements in community empowerment programs are needed to ensure that poverty alleviation policies can be implemented more effectively and sustainably